Internet as a medium in the maintenance of the National and Cultural heritage among Slovenians around the world. The old dilemmas of the new solutions. - Mikola, Maša; Gombač, Jure (Two Homelands, 2008)
The authors use different theories and fieldwork findings to discuss communication and national and cultural heritage of Slovenians abroad in the cyberspace. The fast expanding technology produces numerous changes that significantly influence its users. Recently, the relatively static, one-way communication of the »classic« web pages has been replaced by the interactive forums, pages with uploaded videos, blogs and updated web pages. This makes it more difficult to find criteria for evaluation of the material and define what can be identified as the national and cultural heritage. The material is therefore the entire debate itself, a communication between certain groups of individuals who are discussing values, myths, stereotypes, cultural practices and identities, and subsequently transfer their virtual meetings into the physical world.